Locking up my generation: cohort differences in prison spells over the life course - Shen, Yinzhi (Criminology, 2020)
Crime rates have dropped substantially in the United States, but incarceration rates have remained high. The standard explanation for the lasting trend in incarceration is that the policy choices from the 1980s and 1990s were part of a secular increase in punitiveness that has kept rates of incarceration high. Our study highlights a heretofore overlooked perspective: that the crime-punishment wave in the 1980s and 1990s created cohort differences in incarceration over the life course that changed the level of incarceration even decades after the wave. With individual-level longitudinal sentencing data from 1972 to 2016 in North Carolina, we show that cohort effects—the lingering impacts of having reached young adulthood at particular times in the history of crime and punishment—are at least as large (and likely much larger) than annual variation in incarceration rates attributable to period-specific events and proclivities. The birth cohorts that reach prime age of crime during the 1980s and 1990s crime-punishment wave have elevated rates of incarceration throughout their observed life course. The key mechanism for their elevated incarceration rates decades after the crime-punishment wave is the accumulation of extended criminal history under a sentencing structure that systematically escalates punishment for those with priors.